DETERMINATION OF THE COMPOSITION AND QUANTITY OF MACRO- AND MICROELEMENTS OF THE PLANT WORMWOOD (Scientific journal of the Fergana State University, 2023)
The article presents a study by inductively coupled plasma mass spectrometry of the amount of macro- and microelements in the composition of the leaves and stems of the wormwood plant, growing in the Yozevon district of the Fergana region. In the studied organs of the plant, 22 macro- and microelements were found. Such macroelements as K, Mg, Na, Ca, S, P have been identified. The leaves contain the highest amount of potassium (7410, 072 mg/kg) and the least amount of phosphorus (288,627 mg/kg). Fe, Li, Be, B, Al, Si, Ti, V, Cr, Mn, Co, Ni, and Re were identified among the trace elements. Of the toxic elements, only trace amounts of lead were found in the leaves. depending on the content of elements Based on the elemental composition, it has been shown that the leaves of the plant can be used in various food supplements.